The hidden heir - Webb, Debra (Toronto : Harlequin, 2006)
"After the stunning events of Edward Lazellari's debut fantasy, Awakenings, fourteen-year-old Daniel Hauer is on the run from the law. Even though Daniel acted in self-defense when he accidentally killed his stepfather, he's afraid the authorities will not see it that way. The situation is complicated by the fact that Daniel is the missing heir to the far-off kingdom of Aandor, something Daniel is unaware of. Because he is the key to uniting a warring empire, there are those who are desperate to locate him--but there are also those who wish him never to be found. From the streets of New York City to the back roads of rural North Carolina, the search for Daniel sets powerful factions against each other in a do-or-die battle for the rule of the kingdom of Aandor. Against a backdrop of murder, magic, and mayhem on the streets of New York City, victory goes to the swiftest and the truest of hearts"--
Keywords: Heirs; FICTION / Fantasy / Epic; FICTION / Fantasy / Contemporary